A generalized condorcet jury theorem with two independent probabilities of error - Roland Kirstein; Georg von Wangenheim (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
The Condorcet Jury Theorem is derived from the implicit assumption that jury members only commit one type of error. If the probability of this error is smaller than 0.5, then group decisions are better than those of individual members. In binary decision situations, however, two types of error may occur, the probabilities of which are independent of each other. Taking this into account leads to a generalization of the theorem. Under this generalization, situations exists in which the probability of error is greater than 0.5 but the jury decision generates a higher expected welfare than an individual decision. Conversely, even if the probability of error is lower than 0.5 it is possible that individual decisions are superior.
Keywords: D71; K40; L22; 330; group decisions; judicial; imperfect decision-making; Gerichtsbarkeit; Gruppenentscheidung; Abstimmungsparadoxon; Theorie